The Impact of Audit Fee on Audit Quality in UK - NI, MENGLU (2012)
This thesis investigates the effect of audit fees on audit quality. Audit fees include the normal audit fees and abnormal audit fees. This paper examines how the audit quality proxy by the magnitude of absolute discretionary accruals associated with the abnormal audit fees that we focused on. Through our research, we found that the abnormal audit fees are negatively related to the discretionary accruals. And the sign of the abnormal audit fees will determine the level of audit quality. The ABAFEE is negatively associated with the unsigned discretionary accruals when abnormal audit fees are positive. And when abnormal audit fees are negative, the ABAFEE is positively correlated with the unsigned discretionary accruals. It suggests that the audit quality would not be impaired by the high abnormal audit fees. We also test for other variables relating to the audit quality, and found that non-audit is not significant associated with the discretionary accruals while BIG4 accounting firms with the industry specific auditors help to improve the audit quality than non-BIG4.